ON THE REACTION OF MARINE FISHES IN INTERRUPTED A.C OF 50 Hz - BISWAS, K P (Fishery Technology, 2025)
The reactions of marine fishes i-n interrupted A. C. offuniform electrical fie]d and constant current dt"nsity have beenstudied in order to determine the optimum effective periods of shock:for narcosis and fixation. Higher effective periods were requiredwith gradual decrease in potential difference between head and tail,which in turn depended on the length of fish and its position inelectrical field. The body voltage of fish varied directly with thelength and inversely with the rise of angle between their bodyaxis and field lines. The fish subjected to higher effective pe:riod tooklonger time for recovery from narcosis. The effect of impulsecurrent was manifested by increased rate of giH movements inP!atax tefora, Haetodon ollaris, Crysophus burda, Siganus vermiculatusand Scolopsis leucotaenia, and lowered rate of movementsin others when subjected to different effective periods inespective